Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1158/1078-0432.ccr-15-1722
|View full text |Cite
|
Sign up to set email alerts
|

(Ir)relevance of Metformin Treatment in Patients with Metastatic Pancreatic Cancer: An Open-Label, Randomized Phase II Trial

Abstract: Purpose: We aimed to assess the safety and efficacy of metformin for treating patients with metastatic pancreatic cancer and to identify endocrine and metabolic phenotypic features or tumor molecular markers associated with sensitivity to metformin antineoplastic action.Experimental Design:We designed an open-label, randomized, phase II trial to assess the efficacy of adding metformin to a standard systemic therapy with cisplatin, epirubicin, capecitabine, and gemcitabine (PEXG) in patients with metastatic pan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 49 publications
4
127
0
Order By: Relevance
“…Whereas, the variation in the adjuvant effects of metformin administration could be partially interrupted by the differences in tumor stage, treatment strategy or ethnicity originating from both patient characteristics and tumor biology. Recently, two RCTs with 181 advanced pancreatic cancer patients(60 and 121 patients, respectively) conducted in Caucasian population failed to show a survival benefit for metformin users [26,31]. However, a more recent large cohort study with 764 Asian patients at an early stage(I-II) reported a 27% decrease of death risk for those receiving metformin adjuvant treatment [39], and similar survival benefit was further confirmed in another lager cohort study (3393 patients) in Caucasian patients who received resection and metformin therapy [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, the variation in the adjuvant effects of metformin administration could be partially interrupted by the differences in tumor stage, treatment strategy or ethnicity originating from both patient characteristics and tumor biology. Recently, two RCTs with 181 advanced pancreatic cancer patients(60 and 121 patients, respectively) conducted in Caucasian population failed to show a survival benefit for metformin users [26,31]. However, a more recent large cohort study with 764 Asian patients at an early stage(I-II) reported a 27% decrease of death risk for those receiving metformin adjuvant treatment [39], and similar survival benefit was further confirmed in another lager cohort study (3393 patients) in Caucasian patients who received resection and metformin therapy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pooling analysis by Zhang et al indicated that metformin may improve the survival for cancer patients with concurrent diabetes, particularly for breast, colorectal, ovarian, and endometrial cancer, but they failed to show such survival benefit in pancreatic cancer with only 3 studies included (HR=0.80, 95% CI= 0.62-1.03) [14]. Additionally, a recent meta-analysis combining 27 studies comprising 24178 participants was conducted to qualify the adjuvant effect of metformin in cancers, suggesting a better survival, particularly in colorectal and prostate cancer, however without special attention to pancreatic cancer Reni,2016 [26] Italy ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Lee,2016 [27] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Ambe,2016 [21] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cheon,2014 [28] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Hwang,2013 [29] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Amin,2016 [30] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Kordes,2015 [31] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Chaiteerakij,2016 [32] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Sadeghi,2012 [33] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cerullo,2016 [34] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Kozak,2016 [35] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Toomey,2015 [36] USA ▲ ▲ ▲ ▲ ▲ 5 Choi,2015 [37] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Beg,2017 [38] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Jang,2017 [39] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Frouws,2017 [40] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 E,2017 [41] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 [46] and by E et al (6 studies with 12,057 participants) have represented similar findings with demonstrating a survival benefit of metformin therapy for pancreatic cancer patients [47]. Furthermore, the subgroup analyses based on ethnicity in the current study revealed a more favorable prognosis for metformin therapy in Asian population (HR=0.74, P=0.01) but not evident in Caucasian population (HR= 0.92, P=0.10) which was in line with the findings by Zhou et al, indicating that ethnicity variation may contribute to the metformin action, however, the underlying mechanism for the discrepancy remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,11 Other studies have investigated the impact of metformin use among patients with advanced, unresectable pancreatic cancer. 15,26,27 In one meta-analysis investigating The authors cautioned, however, that the various studies included in the meta-analysis suffered from significant heterogeneity with regard to study design and patient clinical characteristics. 4 In a single institution study, Kozak et al examined the association between metformin use and survival among a cohort of 171 patients with pancreatic cancer and noted an improved OS among patients receiving metformin.…”
Section: Discussionmentioning
confidence: 99%
“…13 While previous studies have suggested that metformin use in patients with neoplastic disease may lead to a longer overall survival and a lower risk of death, data on patients with pancreatic cancer have been limited. 14,15 In particular, prior reports have been limited as patients who underwent surgical resection were not included. Additionally, limited to single institutions, previous reports did not assess the potential effect of metformin in a more generalized national population of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In metformin-related studies, 8 of 10 studies were retrospective cohort, while 2 of 10 studies were randomized clinical trials. Meta-analysis has limited performance with two studies only [59], however, both randomized clinical trials reported that metformin, in combination with current chemotherapy, did not improve pancreatic cancer patients’ survival, compared with patients treated with chemotherapy alone [56, 57]. Metformin treatment may be more beneficial to pancreatic cancer patients diagnosed at a younger age and early cancer stage [60].…”
Section: Discussionmentioning
confidence: 99%